Breast Cancer and Non‐Hodgkin Lymphoma in a Young Male with Cowden Syndrome. Issue 3 (15th October 2015) - Hagelstrom, Robert Tanner; Ford, James; Reiser, Gwendolyn M.; Nelson, Marilu; Pickering, Diane L.; Althof, Pamela A.; Sanger, Warren G.; Coccia, Peter F.
Abstract : Male breast cancer (MBC) is unusual, especially in young adults. Most cases of MBC as a secondary malignancy relate to the previous treatment with ionizing radiation. MBC can be associated with mutations in hereditary cancer predisposition syndrome genes (i.e., BRCA2 ); however, no such association has been reported in patients with Cowden syndrome (involving the phosphatase and tensin homolog [ PTEN ] gene). We describe a patient with Cowden syndrome who was initially diagnosed with B‐cell lymphoblastic lymphoma at the age of 7 years, then MBC at the age of 31 years, and never received radiation therapy.